Effect of surface pretreatment on interfacial chemical bonding states of atomic layer deposited ZrO2 on AlGaN - Ye, Gang (2015)
Atomic layer deposition (ALD) of ZrO2 on native oxide covered (untreated) and buffered oxide etchant (BOE) treated AlGaN surface was analyzed by utilizing x-ray photoelectron spectroscopy (XPS) and high-resolution transmission electron microscopy. Evidenced by Ga–O and Al–O chemical bonds by XPS, parasitic oxidation during deposition is largely enhanced on BOE treated AlGaN surface. Due to the high reactivity of Al atoms, more prominent oxidation of Al atoms is observed, which leads to thicker interfacial layer formed on BOE treated surface. The results suggest that native oxide on AlGaN surface may serve as a protecting layer to inhibit the surface from further parasitic oxidation during ALD. The findings provide important process guidelines for the use of ALD ZrO2 and its pre-ALD surface treatments for high-k AlGaN/GaN metal–insulator–semiconductor high electron mobility transistors and other related device applications.